THE STUDY OF SYNTACTIC LEVEL IN UZBEK LINGUISTICS - Boyatov, Oybek; Ravshanova, Madina (Journal of Higher Education and Academic Advancement, 2024)
Objective: This study aims to investigate the development and study of syntax in Uzbek linguistics by analyzing its historical evolution and identifying the key contributions of each stage. Method: The research employs a historical-comparative approach to divide the development of Uzbek syntax into three distinct stages, analyzing significant works, methodologies, and theoretical advancements associated with each period. Primary and secondary sources, including historical texts and contemporary linguistic studies, were examined to ensure a comprehensive understanding. Results: The analysis reveals that the study of Uzbek syntax has undergone substantial transformation across three stages: the foundational stage, characterized by descriptive methods; the developmental stage, marked by the introduction of structural approaches; and the modern stage, which integrates functional and cognitive paradigms. These shifts have progressively enriched the theoretical and practical understanding of Uzbek syntax. Novelty: By systematically categorizing and examining the historical trajectory of Uzbek syntax, this study provides a clearer framework for understanding its evolution. The findings offer new insights into the interplay of historical, cultural, and linguistic factors influencing the development of syntax in Uzbek linguistics.